2020
DOI: 10.3390/biom11010050
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable and Antimicrobial Active Poly(Catechin) Obtained by Reaction with a Cross-Linking Agent

Abstract: (+)-Catechin is a flavonoid with valuable antioxidant and antimicrobial properties, found in significant amounts in green tea leaves. Polymeric forms of catechin have been obtained by enzymatic reaction, photopolymerization, and polycondensation in designed processes. However, so far, poly(catechin) has not been received in the cross-linking reaction. Reactions with the cross-linking compound allowed for the preparation of antibacterial and antioxidant materials based on quercetin and rutin. The aim of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 33 publications
(43 reference statements)
3
35
0
Order By: Relevance
“…Ball-shaped structures (marked with red circles on Figure 4) could be characterized for the GDE agent. Similar observations were found for polymeric forms of (+)-catechin obtained by crosslinking with GDE [28]. However, the specificity of crosslinking of flavonoids may depend on the electron density and the presence of groups having an electron donation effect.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Ball-shaped structures (marked with red circles on Figure 4) could be characterized for the GDE agent. Similar observations were found for polymeric forms of (+)-catechin obtained by crosslinking with GDE [28]. However, the specificity of crosslinking of flavonoids may depend on the electron density and the presence of groups having an electron donation effect.…”
Section: Resultssupporting
confidence: 80%
“…where A 0 is the absorbance of the reference sample without naringenin and poly(naringenin), and A 1 is the absorbance in the presence of naringenin or the polymeric form of naringenin [28]. Absorbance was measured at 734 nm for the ABTS method and at 517 nm for the DPPH test using a UV spectrophotometer (Evolution 220, Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Inhibition Of Free Radicals (%) = [((A 0 −mentioning
confidence: 99%
See 1 more Smart Citation
“…As reported previously, polymeric compounds of catechin can be obtained by various reaction pathways, such as enzymatic polymerization [92][93][94], photopolymerization [11,86], HCl-catalyzed polymerization [95], polycondensation with aldehydes in the presence of acid catalysts [96][97][98], and cross-linking reactions of catechin with glycerol diglycidyl ether [99]. A study also reported that the complex condensed aromatic compounds of natural tannins result in high thermal resistance [100].…”
Section: Application Of Catechin Photolysismentioning
confidence: 84%
“…Latos-Brozio and Masek reported that a polymeric catechin complex is generated when catechin is placed in a phosphate-buffered solution, subjected to BLI, and dried at 55 • C. This process produces (+)-catechin photo-polymerization, and the polymeric catechin complex exhibits better thermal stability and a better ability to reduce transition metal ions compared with catechin [86,99]. A polymeric complex of catechin can potentially be used as a pro-ecological stabilizing agent, in addition to being applied as a functional additive for polymeric materials, and as a dressing material in medicine [86,99].…”
Section: Application Of Catechin Photolysismentioning
confidence: 99%